TIKRAR METHOD IN LEARNING TO MEMORIZE THE QUR'AN AT THE TAHFIZ MAHKOTA SUFFARO QUR'AN HOUSE - Izzah, Nurul (Al-Mubin, 2025)
This research is motivated by the problems faced by students at Rumah Tahfidz Mahkota Suffaro, namely laziness, lack of motivation, and declining quality of memorization over time. To overcome this problem, the Tikrar method was chosen as the most suitable method in improving student memorization. This study uses a case study approach by collecting data through interviews with key informants, namely students and teachers. Data analysis is carried out through three stages: data reduction, data presentation, and conclusion drawing to ensure the validity of the data. The results of the study show that the selection of the tikrar method is the result of an in-depth evaluation of the quality of student memorization. With the application of this method, students showed significant progress in several aspects: memorization became stronger and maintained, the quality of reading increased in accordance with the rules of tajweed and tartil, and the discipline and motivation of students to continue memorizing the Qur'an increased. The tikrar method not only helps students in achieving memorization targets, but also accustomes them to interpret and understand the essence of reading the Qur'an. These findings prove that the tikrar method is effective as a learning strategy to form quality students who memorize the Qur'an